The effect of Fe content on the microstructure and properties of Cu–3Ti alloy - Di Wang; Qingjuan Wang; Bofan Xu; Kuaishe Wang; Wen Wang; Fengming Qiang; Ke Qiao (Journal of Materials Research and Technology)
This study investigates the effect of Fe content ranging from 0 to 0.6 wt% on the microstructure and properties of Cu–3Ti alloys. In the forged state, the alloy exhibits an equiaxed grain structure. When the Fe content is 0.1 wt%, the grain size increases to 31.39 μm, and when the Fe content is 0.6 wt%, the grain size decreases to 13.76 μm. The electrical conductivity remains stable at approximately 13 % IACS. The addition of Fe reduces the solubility of Ti in Cu, with some Ti atoms being replaced by Fe or forming FeTi phases with Fe, which promotes the precipitation of the β′-Cu4Ti phase, thereby increasing the hardness with increasing Fe content. At 0.6 wt% Fe, the hardness reaches 255.34 HV0.2. After solution treatment at 880 °C for 2 h, the grain size gradually refines with increasing Fe content. However, the addition of Fe results in the formation of FeTi precipitates, which reduces the solubility of Ti in the matrix, leading to softening of the alloy. A 60 % cold-rolling deformation transforms the microstructure into a fibrous grain structure, resulting in a decrease in electrical conductivity but an increase in hardness. Aging treatment indicates that the Cu–3Ti-0.2Fe alloy reaches optimal performance after aging at 450 °C for 120 min, with a peak hardness of 345.18 HV0.2, electrical conductivity of 11.14 % IACS, and tensile strength of 1085 MPa. This balance of properties is attributed to the controlled precipitation of the β′-Cu4Ti phase and the evolution of the dislocation substructure influenced by Fe.